Response of bacterial community metabolites to bacterial wilt caused by Ralstonia solanacearum: a multi-omics analysis - Wei, Chengjian; Liang, Jinchang; Wang, Rui; Chi, Luping; Wang, Wenjing; Tan, Jun; Shi, Heli; Song, Xueru; Cui, Zhenzhen; Xie, Qiang; Cheng, Dejie; Wang, Xiaoqiang (Frontiers in Plant Science, 2024)
The soil microbial community plays a critical role in promoting robust plant growth and serves as an effective defence mechanism against root pathogens. Current research has focused on unravelling the compositions and functions of diverse microbial taxa in plant rhizospheres invaded by Ralstonia solanacearum, however, the specific mechanisms by which key microbial groups with distinct functions exert their effects remain unclear. In this study, we employed a combination of amplicon sequencing and metabolomics analysis to investigate the principal metabolic mechanisms of key microbial taxa in plant rhizosphere soil. Compared to the healthy tobacco rhizosphere samples, the bacterial diversity and co-occurrence network of the diseased tobacco rhizosphere soil were significantly reduced. Notably, certain genera, including Gaiella, Rhodoplanes, and MND1 (Nitrosomonadaceae), were found to be significantly more abundant in the rhizosphere of healthy plants than in that of diseased plants. Eight environmental factors, including exchangeable magnesium, available phosphorus, and pH, were found to be crucial factors influencing the composition of the microbial community. Ralstonia displayed negative correlations with pH, exchangeable magnesium, and cation exchange flux, but showed a positive correlation with available iron. Furthermore, metabolomic analysis revealed that the metabolic pathways related to the synthesis of various antibacterial compounds were significantly enriched in the healthy group. The correlation analysis results indicate that the bacterial genera Polycyclovorans, Lysobacter, Pseudomonas, and Nitrosospira may participate in the synthesis of antibacterial compounds. Collectively, our findings contribute to a more in-depth understanding of disease resistance mechanisms within healthy microbial communities and provide a theoretical foundation for the development of targeted strategies using beneficial microorganisms to suppress disease occurrence.